A functional variant in the neuropeptide S receptor 1 gene moderates the influence of urban upbringing on stress processing in the amygdala. (July 2014) - Streit, Fabian; Haddad, Leila; Paul, Torsten; Frank, Josef; Schäfer, Axel; Nikitopoulos, Jörg; Akdeniz, Ceren; Lederbogen, Florian; Treutlein, Jens; Witt, Stephanie; Meyer-Lindenberg, Andreas; Rietschel, Marcella; et al.
Abstract We have previously shown that urban upbringing and city living were associated with stress-induced activity in the amygdala and the perigenual anterior cingulate cortex (pACC). This finding might link the epidemiological risk factor "urbanicity" to neurobiological mechanisms of psychiatric disorders. However, given the heritability of stress-related phenotypes, it appears likely that genetic factors can modulate the effect of urbanicity on social stress processing. In the present exploratory study, we investigated if a functional sequence variation in the neuropeptide S receptor gene (NPSR1 rs324981) is associated with brain activation patterns under acute psychosocial stress and if it modulates the link between urbanicity and central stress processing. In animals, neuropeptide S has strong anxiolytic effects and it induces hypothalamus-pituitary-adrenal (HPA) axis activation. In humans, rs324981 was found to be associated with anxiety and stress-related phenotypes. Forty-two subjects were exposed to a psychosocial stress task for scanner environments (ScanSTRESS). While no main effect of rs324981 on amygdala and pACC activity was detected, we found a distinct interaction between rs324981 and urban upbringing modulating right amygdala responses. Moreover, right amygdala responses were significantly higher in subjects who also showed a salivary cortisol response to the stress exposure. The present finding of a gene × environment interaction further supports the view that the brain NPS system is involved in central stress regulation. This study provides first evidence for the assumption that a NPSR1 variant modulates brain activation under stress, interacting with the environmental risk factor urban upbringing.